Using Flash Card as Instructional Media to Enrich the Students' Vocabulary Mastery in Learning English - Welliam Hamer; Nur Azmi Rohimajaya (English Department - University of Sultan Ageng Tirtayasa, 2018)
The purpose to be reached in conducting this study is to share information about the use of flash card as instructional media to enrich the students’ vocabulary mastery in learning English. It is true to say that there are lots of instructional media available in such a way that they can be used as the assistance for the teachers to deliver the materials as well as for the students to understand the materials. Accoding to certain research findings done by the students of English department of Sultan Ageng Tirtayasa University, it is recommended that the teachers should apply various media to improve the quality of teaching and learning English in the classroom, such as role play, flash card, and picture series. However, the are many students from elementary school up to university level still get difficulties when they learn English. The students cannot listen carefully and get misunderstanding, they also hesitate to speak English, they do not understand the difficult words when they read English passage, and they cannot write good sentences and/or paragraphs in English as well. From those points above, it is clear that the use of flash card can be expected to be the solution to solve the problems occurred in attempts to increase the vocabulary mastery for the students when learning English. Besides, the use of flash card can also make the vocabulary learning become enjoyable and interesting. Flash card can be an excellent media to be used because there are many students interested in flash card. In flash card they can stimulate their imagination to develop their ideas and they can learn and find new vocabulary.